Successful pregnancy in a patient with pseudomyxoma peritonei following in-vitro fertilization using donor eggs - S A Narvekar; P K VijayKumar; N Shetty; M S Srinivas; K A Rao (Wolters Kluwer Medknow Publications, 2008)
Pseudomyxoma peritonei is a rare, chronic relapsing disease with a guarded prognosis. Here, we describe such a case of a young patient presenting with primary infertility, who conceived following in-vitro fertilization with donor egg and had a successful pregnancy outcome. Literature regarding fertility and pregnancy outcome in this condition is reviewed.